Knowledge Sharing, Organizational Culture, and Perception of Organizational Support as an Effort to Improve The Performance of Small and Medium Industries: Knowledge Sharing, Budaya Organisasi, dan Persepsi Dukungan Organisasi sebagai Upaya Peningkatan Kinerja Industri Kecil Menengah - Maulidafi, Syahhanif Mochammad; Abadiyah, Rifdah (Universitas Muhammadiyah Sidoarjo, 2023)
The research conducted this time has the aim to find out the influence of Knowledge Sharing, Organizational Culture and Perception of Organizational Support on the Performance of Small and Medium Industries (SMEs). This research was conducted in Kampung Klepon village of Bulang district of Prambon district of Sidoarjo.. The research methods used in this study use quantitative approach methods. Sampling used in this study uses non probability sampling methods using total sampling techniques with the total sampling technique with the number of respondents as many as 43 respondents who dambil from 15 IKM klepon makers in Bulang village of Sidoarjo regency. The data analysis technique used in this study uses multiple linear regression with a statistical calculation tool using SPSS version 26.. The results of this study prove that Knowledge Sharing has a partial effect on IKM Performance with a t calculated value of (3.046) while t table amounted to (1.68385), then the value of t calculates > t table, Organizational Culture partially affects the Performance of IKM with a t count value of (3.905) while the value of t table amounted to (1.68385) then the value of t calculated > t table and Organizational Cultural Perception partially affect the performance of IKM with a value of t count t calculated se large (2.451) while the table's t value is (1.68385) then the value t calculates > t of the table.